Seashell porous asphalt – Sustainable road construction - Liew Siaw Ing, Nicole; Putra Jaya, Ramadhansyah; Khairil Azman, Masri; Noram Irwan, Ramli; Mohamad Idris, Ali (2021)
High consumption of aggregate will cause an environmental problem due to the decreasing of natural earth resources. In Malaysia, cockle shell aquaculture areas extend about 10,383.09 ha which has contribute to a production of 78,024.70 tons.